TECHNIQUES FOR FIXED DENTAL RESTORATIONS REMOVAL - CLASSIFICATION, DECISION ON THE CORRECT APPROACH, ADVANTAGES AND DISADVANTAGES - Radostina Vasileva (Peytchinski Publishing, 2021)
Introduction: Fixed dental restorations possess a predefined period of use. Most often they are removed by means of sectioning which renders them unusable. Reasons exist when practitioners shall preserve the restoration, applying conservative approaches for removing. In the literature, apart from the classic destructive technique with sectioning, conservative, semi-conservative and combined techniques for removal are described. The aim of this article is to present a complete classification and description of different approaches to remove permanently and temporarily fixed prosthetic constructions. Materials and methods: A literature study was conducted athe beginning of 2019. Information was gathered using dental textbooks on the topic specified and online scientific databases such as PubMed, ResearchGate, etc. Conclusion Through this article, a conclusion was drawn that a full classification or description of removal techniques for fixed dentures has not been done in the Bulgarian literature so far. It is reported that information for patients about advantages, disadvantages and dangers of removing a permanently cemented restoration is of great importance. Except for the destructive ones, all methods described here may be used when removing temporarily fixated constructions. The selection of the ideal system or a combination depends on the clinical situation. Safest and most atraumatic for underlying structures when removing permanently cemented restorations is the destructive approach. Practitioners must be precisely familiar with the techniques so as to be able to preserve the construction, to avoid any danger connected with the clinical case. According to data gathered, no approach is universally applicable when removing fixed prosthetic restorations.